Conflict of Interest Transactions on Equity Crowdfunding Based Funding Activities in Indonesia - Taurusia Eny, Anak Agung Yuka; Puspita Shara, Made Cinthya (Jurnal Magister Hukum Udayana (Udayana Master Law Journal), 2022)
This research aims to understand the difference between transactions in equity crowdfunding and transactions in the capital market and to determine the urgency of managing the risk of conflict of interest in equity crowdfunding transactions. The method used in this research is normative legal research with a statute approach that is relevant to the object of research and an analytical approach. The resulst of the research conducted a conclusion that in fact equity crowdfunding is part of the capital market, but there are differences in substance that cause both of them to face different mechanisms and risks of implementing financing activities. POJK No. 57/POJK.04/2020 has not fully accommodated the legal needs related to the risk of conflict of interest in the equity crowdfunding sector as Law Number 8 of 1995 regarding the Capital Market has regulated the conflict of interest in the capital market sector.